THE EFFECT OF RETURN ON INVESTMENT AND OPERATING CASH FLOW RATIO ON EARNINGS PER SHARE AT PT. GOLD BATTLE SHIPPING (TEMAS) TBK - M. Djauhari,; Muhammad Yasin,; Jakfar, (International Journal of Innovations in Engineering Research and Technology, 2023)
This study aims to determine whether Return On Investment and Operating Cash Flow Ratio affect Earning Per Share at PT Pelayaran Tempuran Emas (TEMAS) Tbk. Period 2017 – 2020. The population in this study is quarterly financial report data for the period 2017-2020. The sampling technique used was purposive sampling technique. Data analysis technique using multiple linear regression analysis. The results of the study show that: Return on Investment does not necessarily affect the level of a company's Earning Per Share, nor does Return On Investment affect the level of Earning Per Share. And Return On Investment and Operating Cash Flow Ratio simultaneously have no significant effect on Earning Per Share.